Karakterisasi Morfofisiologi dan Hasil Minyak 10 Genotip Nilam (Pogostemon cablin Benth.) - Retno Wulansari; Muhammad Tahir; Wiwik Indrawati; Dewi Riniarti (Politeknik Negeri Lampung, 2018)
Characterization of morphophysiology and oil yield of 10 patchouli genotypes (Pogostemon cablinÂ Benth.) aims to test the morphology and physiology character of nine genotypes Aceh patchouli and one comparative clone (Lhokseumawe), obtain high yield oil clones (weight plant and essential oil content), and obtain genetic and phenotypic variabilities that can be used as a new genotype selection indicators. The research was conducted at Experimental Field and Plant Laboratory of the State Polytechnic of Lampung in April until November 2016. This research used Randomized Block Design (RBD) with 10 treatment levels and 3 replications.The LSI test results on the physiological character of the nine genotypes and one comparative clone showed that NPL 9 genotypes superior to the variables of the angle of petiole, chlorophyll content, leaf area, specific leaf area, and leaf area index. The NPL 9 genotypes resulted higher yield and rendement yields than other genotypes tested and one comparator, that was 2,36%. The character of stem production and rendement has a genetic variant value greater than the environmental variant. For genetic variability and phenotypic variability in the variables observed relatively uniform so that can not be used as an indicator of selection.Â Â Keywords: Aceh patchouli, leaf character, selection indicator, variability of genotype, variability of phenotype